IMPLEMENTASI E-BUSINESS UNTUK PENINGKATAN PEMASARAN DAN ADMINISTRASI DI MADRASAH IBTIDAIYAH - Muhammad Dzakaaul Fikri; Umi Awaliatul Laely; Euis Desyafitri; Rina Widianingsih; Rochanda Wiradinata; Ahmad Ripai (LP2M IAIN Sultan Amai Gorontalo, 2026)
This study aims to evaluate the implementation of e-business in improving the effectiveness of marketing and administrative processes at Madrasah Ibtidaiyah (MI) An-Nur, Cirebon Regency. The research is motivated by the need for Islamic primary education institutions to adapt to digital technology to address the inefficiencies of manual systems. A descriptive qualitative approach was used, with data collected through observation, semi-structured interviews, and documentation over one week. Data were analyzed using the Miles, Huberman, and Saldana model, which includes data reduction, data display, and conclusion drawing. The findings indicate that e-business implementation through social media and digital platforms such as Google Workspace has significantly enhanced promotional effectiveness and administrative efficiency. Student enrollment increased by 28–30%, and administrative processing time decreased by up to 40%. Additionally, service transparency and parental involvement in the educational process improved. However, several challenges were identified, including limited technological infrastructure, staff resistance to digital change, and data security issues. The study concludes that e-business is an effective strategy to develop a more modern, professional, and competitive madrasah. Continuous efforts in infrastructure development, staff training, and digital security policy enhancement are necessary.